Gelişimsel Kalça Displazisinde Pavlik Bandajı ile Tedavinin Başarısını Etkileyen Faktörlerin Kısa Süreli Takiple Değerlendirilmesi - (:unkn) unknown (My University, 2015)
Amaç: Gelişimsel kalça displazisinin (GKD) Pavlik bandajı ile tedavisinin başarısını etkileyen faktörleri kısa süreli takiple de- ğerlendirmek. Gereç ve Yöntem: Çalışmamızda ultrasonografi (USG) ile GKD tanısı konup Pavlik bandajı ile tedavi edilen 0-6 ay arası 55 hasta (76 kalça) incelendi. Tedavi başlangıcındaki fizik muayene bulguları, GKD açısından tanımlanmış risk faktörleri, kalçaların Graf metoduna göre tipleri ve tedavi başlangıç yaşı ile Pavlik bandajı tedavisinin sonuçları karşılaştırıldı. Elde edilen verilerin tedavi sonucuna etkileri analiz edildi. Bulgular: Pavlik bandajı ile tedaviye başlama yaşı ortalama 2.80±1.97 ay, Pavlik bandajı kullanım süresi 3.80±1.73 ay, ortalama takip süresi 20.9 ay (6-46 ay) idi. Hastaların 48inde (68 kalça-%89.5) Pavlik bandajı ile tedavi başarılı olurken, yedisinde (8 kalça-%10.5) kapalı redüksiyon ve pelvi-pedal alçı yapılması gerekti. Tedavi öncesi kalçanın disloke (Graf tip 3 ve 4) olması (p=0.010), makat gelişi (p=0.030) ve kundak kullanım öyküsü varlığı (p=0.003) çok değişkenli analizde Pavlik bandajı tedavisinin başarısını olumsuz etkileyen faktörler olarak tespit edildi. Sonuç: Tedaviye başlama yaşı ile kundak kullanımı başarı oranı- na etki eden değiştirilebilir faktörlerdir. Tarama ile GKD olguları erken saptanarak tedavi başarısı artırılabilir. Ayrıca ülkemizde halen sorun olan kundak ile mücadele edilerek GKD riski azaltı- labileceği gibi, Pavlik bandajı ile erken dönem tedavinin başarısı da artırılabilir.

Background: The aim of this study is to assess the factors affecting the success of early treatment for developmental dysplasia of the hip (DDH) with the Pavlik harness over the course of short-term clinical follow up. Methods: We evaluated the medical records pertaining to 55 patients (76 hips) who were diagnosed with DDH by ultrasonography (USG) and treated using the Pavlik harness. Physical examination findings at the beginning of treatment, risk factors associated with DDH, hip types as determined by the Graf method, and age at the start of treatment were evaluated as potential factors related to the results of Pavlik harness treatment. Results: The average age at the time of treatment by Pavlik harness was 2.80±1.97 months. Mean usage time was 3.80±1.73 months and mean follow-up time was 20.9 months (6-46 months). While treatment with the Pavlik harness was successful in 48 patients (68 hips-89.5%), 7 patients (8 hips-10.5%) exhibited closed reduction and hip spica cast. Multivariate analysis identified the presence of a dislocated hip (Graf type 3 and 4) (p=0.010), breech presentation (p=0.030), and history of swaddle (p=0.003) as factors adversely affecting the success of a Pavlik harness treatment. Conclusion: Age at the start of treatment and the use of swaddling are modifiable factors that affect treatment success rate. The rate of treatment success is increased by early detection of DDH cases through proper screening. The risk of the DDH can be reduced and efficacy of treatment interventions improved through the education of parents regarding swaddling techniques
Evaluation and Short-Term Follow-Up of the Factors Affecting the Success of Pavlik Harness Treatment for Developmental Dysplasia of the Hip
Keywords: Genel ve Dahili Tıp